2009
DOI: 10.1051/0004-6361/200811136
|View full text |Cite
|
Sign up to set email alerts
|

The baryonic Tully-Fisher relation and its implication for dark matter halos

Abstract: Context. The baryonic Tully-Fisher relation (BTF) is a fundamental relation between baryonic mass and maximum rotation velocity. It can be used to estimate distances, as well as to constrain the properties of dark matter and its relation with the visible matter. Aims. In this paper, we explore if extremely low-mass dwarf galaxies follow the same BTF relation as high-mass galaxies. We quantify the scatter in the BTF relation and use this to constrain the allowed elongations of dark matter halo potentials. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
122
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(139 citation statements)
references
References 47 publications
6
122
1
1
Order By: Relevance
“…Pfenniger & Revaz (2005) showed that a marginal improvement in the scatter of the BTFR of McGaugh et al (2000) could be obtained by treating η as a free parameter and suggested that the best-fit value (η ≈ 3) implied additional dark baryonic mass in the disk. In more accurate data, the scatter is consistent with being caused entirely by observational uncertainties (Verheijen 2001;McGaugh 2005b;Stark et al 2009;Trachternach et al 2009;McGaugh 2011), nullifying this motivation for dark baryons.…”
Section: Other Forms Of Gasmentioning
confidence: 76%
See 3 more Smart Citations
“…Pfenniger & Revaz (2005) showed that a marginal improvement in the scatter of the BTFR of McGaugh et al (2000) could be obtained by treating η as a free parameter and suggested that the best-fit value (η ≈ 3) implied additional dark baryonic mass in the disk. In more accurate data, the scatter is consistent with being caused entirely by observational uncertainties (Verheijen 2001;McGaugh 2005b;Stark et al 2009;Trachternach et al 2009;McGaugh 2011), nullifying this motivation for dark baryons.…”
Section: Other Forms Of Gasmentioning
confidence: 76%
“…The latter is a flux-weighted integral over the velocity field and lacks the clear physical meaning of a rotation curve. It is, however, readily obtained from single disk 21 cm observations, whereas obtaining and analyzing interferometric data cubes is considerably more effort intensive (e.g., de Blok et al 2008;Trachternach et al 2009). …”
Section: Rotation Velocitymentioning
confidence: 99%
See 2 more Smart Citations
“…Among these relations, the Baryonic Tully-Fisher relation (hereafter BTFR, e.g. McGaugh et al 2000;Bell & de Jong 2001;Gurovich et al 2004;McGaugh 2005;Pfenniger & Revaz 2005;Begum et al 2008;Trachternach et al 2009;Stark et al 2009;Gurovich et al 2010;Zaritsky et al 2014), extension of the Tully-Fisher relation (hereafter TF, e.g. Tully & Fisher 1977;Pierce & Tully 1988;Teerikorpi 1995;Giovanelli et al 1997b;Courteau & Rix 1999;Tully & Pierce 2000;Giovanelli et al 1997a;Karachentsev et al 2002;Bedregal et al 2006;Noordermeer & Verheijen 2007;Springob et al 2007;Williams et al 2010;Tully & Courtois 2012;Mocz et al 2012;Rawle et al 2013;Torres-Flores et al 2013;Sorce et al 2013Sorce et al , 2014b to the low luminosity galaxies, is often used to constrain and test galaxy formation and evolution models, with various computational methods, in the ΛCDM scenario as well as in alternative theories (e.g.…”
Section: Introductionmentioning
confidence: 99%